2016
DOI: 10.3389/fncel.2016.00080
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Profile of Ion Channel Specializations in the Avian Nucleus Magnocellularis

Abstract: Ultrafast and temporally precise action potentials (APs) are biophysical specializations of auditory brainstem neurons; properties necessary for encoding sound localization and communication cues. Fundamental to these specializations are voltage dependent potassium (KV) and sodium (NaV) ion channels. Here, we characterized the functional development of these ion channels and quantified how they shape AP properties in the avian cochlear nucleus magnocellularis (NM). We report that late developing NM neurons (em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
99
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 59 publications
10
99
0
Order By: Relevance
“…; Hong et al . ). Based on previous findings, we hypothesized that K v 3‐containing channels play a major role in regulating the rapid firing capability NM neurons.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…; Hong et al . ). Based on previous findings, we hypothesized that K v 3‐containing channels play a major role in regulating the rapid firing capability NM neurons.…”
Section: Resultsmentioning
confidence: 94%
“…Our previous study recorded APs at near‐physiological temperature (∼35°C) and we showed a significant improvement of AP kinetics for NM neurons (Hong et al . ). For example, AP half‐width was reduced by ∼30% and fall rate increased by ∼40% when increasing the temperature to ∼35°C.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…D , Population data showing the number of APs elicited as a function of current injections from 0 to 200 pA, steps of 20 pA. NMc1/NMc2 neurons are divided into three subgroups: neurons displaying voltage responses similar to the neurons shown in A , B , and C are noted as A-like, B-like, and C-like, respectively (see Results for objective classification details). Mid- to high-frequency NM neurons (M-HF) are also shown as a reference (data modified from Hong et al, 2016). E , F , Population data showing resting membrane potential (RMP, E ) and input resistance ( F ) of A-like, B-like, and C-like NMc1/NMc2 neurons.…”
Section: Resultsmentioning
confidence: 99%